Global eating, learning from other cultures - Schrank, Jeff; Geefay, Ernie; Learning seed (Lake Zurich, IL : Learning Seed, 2003)
This video study the eating habits through Mediterranean diet, Asian diet and Mexico diet in order to gain useful and tasty ideas in prevent obesity
Title from title screen
Editors, Greg Boyer, Ernie Geefay
Keywords: Reducing diets; Obesity; Food